2017
DOI: 10.3389/fnagi.2017.00291
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Changes in Perirhinal Cortex Sensitivity to Configuration and Part Familiarity and Connectivity to Visual Cortex

Abstract: The perirhinal cortex (PRC) is a medial temporal lobe (MTL) structure known to be involved in assessing whether an object is familiar (i.e., meaningful) or novel. Recent evidence shows that the PRC is sensitive to the familiarity of both whole object configurations and their parts, and suggests the PRC may modulate part familiarity responses in V2. Here, using functional magnetic resonance imaging (fMRI), we investigated age-related decline in the PRC’s sensitivity to part/configuration familiarity and assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 73 publications
3
7
0
Order By: Relevance
“…Barense and colleagues found that the PRC plays a critical role in border familiarity effects on figure assignment 52 and proposed that the PRC modulates activity in the lower level visual area V2. Subsequent studies reported evidence consistent with this proposal 53,54 ; this evidence is consistent with the idea that memory representations of objects are integrated with the input, as we hypothesize here (although we note that there is no evidence that feedback from the PRC in particular mediates the present results).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Barense and colleagues found that the PRC plays a critical role in border familiarity effects on figure assignment 52 and proposed that the PRC modulates activity in the lower level visual area V2. Subsequent studies reported evidence consistent with this proposal 53,54 ; this evidence is consistent with the idea that memory representations of objects are integrated with the input, as we hypothesize here (although we note that there is no evidence that feedback from the PRC in particular mediates the present results).…”
Section: Discussionsupporting
confidence: 92%
“…The effects seen in this study may be mediated by feedback from high-level brain regions representing object memories. Recently, the perirhinal cortex (PRC) of the medial temporal lobe (MTL), traditionally considered exclusively a memory-related structure, has been implicated in object perception [48][49][50][51][52][53][54] . Barense and colleagues found that the PRC plays a critical role in border familiarity effects on figure assignment 52 and proposed that the PRC modulates activity in the lower level visual area V2.…”
Section: Discussionmentioning
confidence: 99%
“…Barense and colleagues found that the PRC plays a critical role in border familiarity effects on figure assignment 49 and proposed that the PRC modulates activity in the lower level visual area V2. Subsequent studies reported evidence consistent with this proposal 5051 ; this evidence is consistent with the idea that memory representations of objects are integrated with the input, as we hypothesize here (although we note that there is no evidence that feedback from the PRC in particular mediates the present results).…”
Section: Discussionsupporting
confidence: 92%
“…The effects seen in this study may be mediated by feedback from high-level brain regions representing object memories. Recently, the perirhinal cortex (PRC) of the medial temporal lobe (MTL), traditionally thought to be exclusively a memory-related structure, has been implicated in object perception 4551 . Barense and colleagues found that the PRC plays a critical role in border familiarity effects on figure assignment 49 and proposed that the PRC modulates activity in the lower level visual area V2.…”
Section: Discussionmentioning
confidence: 99%
“…A set of stimuli originally used in experiments with brain-damaged participants, the “Object Memory Effects on Figure Assignment” (OMEFA) set has been used extensively [18 – 20]. Barense et al [18, 21, 22] tested figure assignment with Inverted Part-Rearranged displays as well. Recently, we modified the borders of the OMEFA stimuli, producing high-resolution images; we also eliminated some items and added others.…”
Section: Figurementioning
confidence: 99%